2015
DOI: 10.1090/tran/6561
|View full text |Cite
|
Sign up to set email alerts
|

On compactly generated torsion pairs and the classification of co-$t$-structures for commutative noetherian rings

Abstract: Abstract. We classify compactly generated co-t-structures on the derived category of a commutative noetherian ring. In order to accomplish that, we develop a theory for compactly generated Hom-orthogonal pairs (also known as torsion pairs in the literature) in triangulated categories that resembles Bousfield localization theory. Finally, we show that the category of perfect complexes over a connected commutative noetherian ring admits only the trivial co-t-structures and (de)suspensions of the canonical co-t-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Following an idea from [, Theorem 4.10], we consider the following assignment. Theorem The map normalΨ which assigns to a torsion pair in D(A) generated by a set of compact objects scriptS the torsion pair in D(Aop) generated by S defines a bijection between (i)compactly generated torsion pairs in D(A), (ii)compactly generated torsion pairs in D(Aop), which restricts to a bijection between (i)compactly generated t‐structures in D(A), (ii)compactly generated co‐t‐structures in D(Aop), and maps intermediate t‐structures to cointermediate co‐t‐structures, and vice versa.…”
Section: Classification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following an idea from [, Theorem 4.10], we consider the following assignment. Theorem The map normalΨ which assigns to a torsion pair in D(A) generated by a set of compact objects scriptS the torsion pair in D(Aop) generated by S defines a bijection between (i)compactly generated torsion pairs in D(A), (ii)compactly generated torsion pairs in D(Aop), which restricts to a bijection between (i)compactly generated t‐structures in D(A), (ii)compactly generated co‐t‐structures in D(Aop), and maps intermediate t‐structures to cointermediate co‐t‐structures, and vice versa.…”
Section: Classification Resultsmentioning
confidence: 99%
“…Remark Beware that the use of terminology and notation may vary in the literature. For example, torsion pairs as above are termed ‘complete Hom‐orthogonal pairs’ in , while torsion pairs according to [, Definition I.2.1] are in fact t ‐structures. Co‐ t ‐structures are called weight structures in .…”
Section: Torsion Pairsmentioning
confidence: 99%
“…, for a non-positive ) are precisely the Milnor colimits of sequences of the form (4), where the cone of each , denoted by , is a coproduct of objects from (resp. of objects from ), for each (see the proof of [40, theorem 8.3.3] for , and [28, theorem 12.2] and [47, theorem 2] for ) (see also [57, theorem 3.7]).…”
Section: Preliminariesmentioning
confidence: 99%
“…(1) It is shown in [1] that, in a compactly generated triangulated category T , the orthogonal S ⊥ to a set S of compact objects (or, equivalently, the orthogonal S ⊥ to the pure-projective object S obtained as the coproduct of all objects in S) is a torsionfree class. In [52] it is then shown that the subcategory S ⊥ is also a torsion class if the category T is furthermore assumed to be algebraic. The statement (1) of the Corollary is a slight generalisation of this second fact.…”
Section: Torsion Pairs In Algebraic Triangulated Categoriesmentioning
confidence: 99%